Transformers : um novo cinema de atrações? pós continuidade e visualidade neobarroca como espetáculo no cinema de ação contemporâneo - Rodrigues Junior, Radael Rezende (2016)
The cinema has often had a strong connection with the narrative, connecting its essence to telling a story through the overlapping of plans and the scene concatenation. However, from the year 2000 onward, motion pictures have been produced where the narra